Response of Vegetable Cowpea to Complete Nutrient Supply Through Foliar Application - V. Vasuki; Muli Naga Surekha; Swathy Ullas; Swathi Dash; Prasanna Kumar, K.; V. Revathi (Archives of Current Research International, 2025)
In vegetable cowpea, pot culture experiments were conducted to study effect of crop response to complete nutrient supply through foliar application of nutrients in randomized block design with three replications and eight treatments including, Control (no nutrients), Soil application of nitrogen (N), phosphorus (P), potassium (K) alone and along with micronutrients (MN), Foliar application of 2% N alone, P alone, K alone, and in combination of 2% of N, P, K each and 0.5% MN. Soil application of recommended dose (RD)of NPK and MN done at 4 Days After Sowing (DAS). Foliar application of nutrients done at 30 DAS, 40 DAS and 50 DAS. Results revealed, soil application of recommended dose of fertilizers (RDF) NPK + MN recorded highest growth parameters like plant height, number of leaves per plant and highest yield parameters like dry weight per plants, number of pods per plant, fresh pod yield per plant and was comparable with foliar application of 2% N + 2% P + 2% K + 0.5% MN. Post-harvest soil sample analysis for soil nitrogen, phosphorus and potassium status, the soil nitrogen status was highest in foliar application of 2% N + 2% P + 2% K + 0.5% MN and lowest in soil application RDF NPK, soil phosphorus was highest in RDF NPK and soil potassium status was higher in control.